2015
DOI: 10.1007/s10853-015-9084-z
|View full text |Cite
|
Sign up to set email alerts
|

Silane functionalization of graphene oxide and its use as a reinforcement in bismaleimide composites

Abstract: Silane-functionalized graphene oxide (GO) nanosheets were synthesized by chemically grafting cmethacryloxypropyltrimethoxysilane (MPTS) onto GO sheets. The resulting MPTS-functionalized GO (MPTS-GO) nanosheets were characterized by Fourier transform infrared spectroscopy, energy dispersive X-ray analysis, X-ray photoelectron spectra, X-ray diffraction, and Raman spectroscopy. Bismaleimide (BMI) composites filled with GO and MPTS-GO were prepared at different filler loading levels. The study showed that the exf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…This suggests that covalent bonding was created between the silane coupling agent and Gr with a little destruction of the lattice. This was in line with the literature …”
Section: Resultssupporting
confidence: 94%
“…This suggests that covalent bonding was created between the silane coupling agent and Gr with a little destruction of the lattice. This was in line with the literature …”
Section: Resultssupporting
confidence: 94%
“…For instance, addition of Mg, Ti, and Ni has an effect on the quality and appearance of the anodic alumina film, 16 and furthermore such oxide films have been found to be more stable at high pH environments. It is also known that in an aqueous environment, pure aluminum forms a thin passive film (surface oxide layer) with a typical thickness of 2-4.3 nm, similar to that formed in air.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the modification of BMI resins with the nanomaterial. Researchers have reported that the inclusion of low weight percentages (≈1 wt%) of graphene oxide, the oxidised version of graphene that exhibits better processing characteristics, but significantly poorer conductivity, can lead to enhancements in impact strength of 37 % [126,127].…”
Section: Graphenementioning
confidence: 99%